2004
DOI: 10.1002/sca.4950260608
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic scanning electron microscope design

Abstract: Summary: This paper describes a proposal to improve the design of scanning electron microscopes (SEMs). The design is based upon using an SEM column similar to the conventional one, magnetic sector plates and a mixed field immersion objective lens. The optical axis of the SEM column lies in the horizontal direction and the primary beam is turned through 90 degrees before it reaches the specimen. This arrangement allows for the efficient collection, detection and spectral analysis of the scattered electrons on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the previous spectroscopic SEM proposal made by the present authors [5], a square magnetic sector unit was proposed, based upon its success reported for the low energy electron microscope (LEEM) by Tromp et al [7]. However, the present work shows that in the context of the spectroscopic SEM design, a circular sector unit is more suitable.…”
Section: The Circular Magnetic Sector Unitmentioning
confidence: 72%
See 2 more Smart Citations
“…In the previous spectroscopic SEM proposal made by the present authors [5], a square magnetic sector unit was proposed, based upon its success reported for the low energy electron microscope (LEEM) by Tromp et al [7]. However, the present work shows that in the context of the spectroscopic SEM design, a circular sector unit is more suitable.…”
Section: The Circular Magnetic Sector Unitmentioning
confidence: 72%
“…For the previous spectroscopic SEM design by the present authors [5], in order to achieve low aberrations and operate with stigmatic focusing conditions, it was assumed that the sector's outer plate excitation should be around three times greater than the inner plate excitation, have the same sign, and that the incoming primary beam should project a focus point into the centre of the sector unit. These operating conditions were reported by Tromp et al for LEEM [7].…”
Section: The Circular Magnetic Sector Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a ''Spectroscopic scanning electron microscope (SEM)'' proposal made by Khursheed et al [1,2] describes the possibility of redesigning the SEM so that it can capture the entire energy range of scattered electrons that leave the specimen. The new design, depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This understanding informed the design of the low-energy electron microscope (LEEM) [ 10 , 11 ]. LEEM has supported complex studies in materials science [ 12 – 15 ]. However, in LEEM, the sample is generally irradiated with a flood beam and uses complex instrumentation of magnetic sector plates to separate electrons leaving the sample from the primary beam.…”
Section: Introductionmentioning
confidence: 99%